(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): What are the external factors that impact the implementation of market health services in health institutions? Purpose: The purpose of the article is to determine which external factors impact our healthcare system and consequently provide an opportunity for the implementation of market-based healthcare services. Method: The article will use a descriptive method based on the study of domestic and foreign literature, which will be supported by analyzing data from external factors in Slovenia and abroad. Results: In the research, we included external factors that mutually influence the healthcare system in Slovenia and enable the increased implementation of market healthcare activities. The monitoring of external factors predicts the needs of the population and trends in the development of Slovenian healthcare. With the help of the results in the article, decision-makers can take a comprehensive approach to solving the problem of accessibility to health services. Organization: The results of the research represent guidelines for health institutions to increase the implementation of market health services due to changes in external factors affecting the public health system. Society: By including health institutions in the implementation of market health activities, patients can obtain quality health care and faster treatment that the public health network cannot provide. Originality: The article brings together external factors that have the greatest indirect impact on our healthcare system and accessibility to healthcare services in the future. Limitations/Future Research: Limitations were evident in the accessibility of data on different websites or the same time frame of published data. Even during the data processing itself, we were faced with meaningful grouping of data in order to obtain useful data for analysis.